STRATEGI GURU DALAM MENINGKATKAN KEAKTIFAN SISWA PADA PROSES PEMBELAJARAN DI KELAS IX MTS SWASTA KURNIA KOTO SALAK - Rina; Atina husna; Nurul afifah; Meta yupitri zoningsih; Muhammad arifin; Muhammad Fauzi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze teacher strategies in enhancing student activeness during thelearning process in grade IX at MTs Swasta Kurnia Koto Salak. The background lies in thecrucial role of teachers in creating participatory learning, where students are not merelyknowledge receivers but active contributors in the classroom. Teachers are expected todesign innovative, interactive, and relevant strategies that align with learners’ needs.Thestudy employed a qualitative approach with a case study design. Data were collectedthrough participant observation, in-depth interviews with teachers and students, andlearning document analysis. The data were analyzed descriptively by identifying,categorizing, and interpreting strategies applied by teachers.Findings reveal that teachersimplemented participatory methods such as discussion forums, interactive questioning, andcollaborative group work. The effectiveness is reflected in student activeness percentages:participatory methods 85%, classroom management 80%, and creative media utilization75%. Challenges include limited time, varying student abilities, and insufficient learningfacilities.The study concludes that teacher strategies are effective in enhancing studentactiveness, though challenges remain. It implies the need for continuous innovation inteaching strategies, strengthening classroom management, and institutional support inproviding adequate learning media.